Immediate effects of TENS and HVPS on pain and range of motion in subacromial pain syndrome: A randomized, placebo-controlled, crossover trial - Bilek, Furkan; Karakaya, Mehmet Gurhan; Karakaya, Ilkim Citak (Ios Press, 2021)
BACKGROUND: Transcutaneous electrical nerve stimulation (TENS) is one of the most common methods for managing shoulder pain, and high voltage pulsed currents (HVPS) may be used for reducing pain. However, their immediate effects on resting pain and pain-free active range of shoulder motion (pfROM) in patients with subacromial pain syndrome (SAPS) have not been studied comparatively, yet. OBJECTIVES: The aim of this study was to compare the immediate effects of TENS, HVPS and placebo stimulation on shoulder resting pain and pfROM in patients with SAPS. METHODS: Randomized, placebo-controlled, double-blind, crossover study. One hundred and six patients with SAPS received placebo (predetermined 1st day application), TENS and HVPS with 1-day interval, in a random sequence. Before and after each application, resting pain and pfROM were evaluated by 0-10 cm visual analogue scales and a digital inclinometer, respectively. RESULTS: Intensity of pain decreased significantly after TENS, HVPS and placebo interventions (p < 0.05). While pfROMs increased significantly after TENS and HVPS ( p < 0.05), remained unchanged after placebo, except for internal and external rotations ( p > 0.05). The most obvious effects on pain and pfROMs occurred after HVPS ( p < 0.05). CONCLUSION: In patients with SAPS, both HVPS and TENS, but preferably HVPS can be used effectively to decrease pain and increase pfROM.
Keywords: Shoulder pain; joint range of motion; electrotherapy; physiotherapy; orthopedics; transcutaneous electrical nerve stimulation; high voltage pulsed currents